PENINGKATAN HASIL BELAJAR KIMIA MATERI HIDROLISIS GARAM MENGGUNAKAN MODEL PEMBELAJARAN LEARNING CYCLE PADA PESERTA DIDIK KELAS XI IPA SMA NEGERI 1 BANJARNEGARA SEMESTER GENAP TAHUN PELAJARAN 2011/2012 - Sunardi Sunardi (Sainteks, 2013)
This study aims to improve the learning outcomes of chemical hydrolysis of the salt material using learning model Learning Cycle In Class XI Science Students SMA Negeri 1 Banjarnegara Academic Year 2011/2012. Research subjects class XI IPA-3. The process of learning chemistry in schools tends to focus on the teacher (teacher centered), textbook-centered, low learning outcomes with a mean 67 to 60% level learning outcomes have not reached complete study, the lack of ability of students to learn on their own and in groups so that the teacher as the source of learning dominant class. The action consisted of two cycles, each cycle consisting of four phases: Plan, Perform Action, action observation, and reflection. Data analysis using descriptive analysis techniques comparative value of the learning cycle, second cycle and qualitative descriptive analysis. The results of learning activities, the value of learning outcomes, learning ketuntasa learning activity increased in the first cycle (62.86%), cycle II (80%). Value of individual learning outcomes (cycle I, mean 67.71) and (cycle II, average 80.57). Mastery learning individually (cycle I, 42.82%) and (cycle II, 82.87%). Mastery learning in groups (cycle I, 62.5%) and (cycle II, 87.5%). Based on the data analysis and discussion of the research results, it can be concluded Learning Cycle teaching model to improve learning outcomes chemical hydrolysis of the salt material. Keywords: Learning Cycle, Learning Outcomes, Chemistry